If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y = y Solving 2x + -1y = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 2x + -1y + y = y + y Combine like terms: -1y + y = 0 2x + 0 = y + y 2x = y + y Combine like terms: y + y = 2y 2x = 2y Divide each side by '2'. x = y Simplifying x = y
| .2x+.4(5)=.3(x+2) | | 15y+3=20y+8 | | -29=5v+6-12v | | -5=2a | | 2x+49=6x+13 | | 8x+8=3x+28 | | -2(5+6m)+16=6 | | 23x+34=23-23x+7x | | 6x=1500 | | 5x-16=39 | | 5x-3y=24 | | -13=2a-8 | | 5x+21=-2x-14 | | 2x+7=5x+16 | | 28+10x=6x-4 | | 20x=24x+16 | | 6z-3=9+4x | | -4(2x-5)+3x=x-28 | | M-13=8 | | 7(a-1)+4=-(2a-4)+6a+2 | | 8x-5=3(x+7) | | -8(p-3)=8 | | 21x+100=11x-10 | | 3x^3+15x^2-42x=0 | | 2x-x+9+3x-2=16 | | 56x-50x=256 | | -6-(-3)=x | | 6z-3=9+4z | | 6(-1)-(-3)=-3 | | 8-6x=-6 | | x+4x=-4x-81 | | x^3+10x^2+74x=0 |